2012
DOI: 10.21273/hortsci.47.9.1210
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Methods for Mitigating Invasiveness of Woody Ornamental Plants: Research Needs and Opportunities

Abstract: Because cultivation of exotic woody ornamental plants has led to establishment of a number of invasive species, there is considerable interest in breeding methods to reduce the propensity for spread. We review progress in conventional breeding and transgenic biotechnology approaches to producing sterile forms of ornamental woody plants. Conventional forms of inducing sterility, including induction of polyploidy, interspecific hybridization, and mutagenesis, are generally inexpensive and can be applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 67 publications
(79 reference statements)
0
33
0
Order By: Relevance
“…There are widespread concerns over gene flow and dispersal of genetically engineered and invasive exotic plants (Brunner et al ., ; Vining et al ., ; Strauss et al ., ). The conserved function of AG and STK in Populus , as confirmed by our study, could provide an important tool for genetic containment in Populus , and likely in many other plant taxa.…”
Section: Discussionmentioning
confidence: 99%
“…There are widespread concerns over gene flow and dispersal of genetically engineered and invasive exotic plants (Brunner et al ., ; Vining et al ., ; Strauss et al ., ). The conserved function of AG and STK in Populus , as confirmed by our study, could provide an important tool for genetic containment in Populus , and likely in many other plant taxa.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that overexpression of exogenous FT genes in eucalypts can be an effective means for acceleration of eucalypt tree breeding. This approach is also valuable as a general research tool for genetic studies, as well as for those focused on genetic modification of flower structure and fertility (Brunner et al, 2007;Vining et al, 2012). Its practical implementation will depend on regulations and market restrictions if null segregants are considered GMOs, and on improvements to transformation efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…There are a variety of potential and demonstrated options for GEbased reproduction modification in trees (reviews in Brunner et al, 2007;Vining et al, 2012). In addition to the goal of containment, reproductive modification also has been sought as a means to improve vegetative growth by increased allocation of photosynthetic resources (Strauss et al, 1995), reduce the production of Table 1 Examples of field trials of genetically engineered (GE) trees that have showed efficacy or promise in delivery of target traits Tree species Trait allergenic pollen and decrease nuisance reproductive tissues in urban trees.…”
Section: Ge Reproductive Modificationmentioning
confidence: 99%